Monitoring Oxygen Concentration and Humidity Parameters of Bubble CPAP Based on IoT - Puspitasari, Ratna Ika; Titisari, Dyah; Lusiana, Lusiana; Lamidi, Lamidi (Jurnal Teknokes, 2023)
Existing Bubble Continuous Positive Airway Pressure (CPAP) devices used in neonatal care. Specifically, the lack of digital result display and monitoring capabilities for oxygen concentration and humidity parameters is identified as a major issue. This study aims to address the shortcomings of existing Bubble Continuous Positive Airway Pressure (CPAP) devices used in neonatal care by designing a monitoring system for oxygen concentration and humidity parameters. The lack of digital result display and monitoring capabilities for oxygen rate, concentration, temperature, and humidity necessitates an improved solution. The proposed system utilizes Internet of Things (IoT) technology, allowing remote monitoring by healthcare professionals. Oxygen concentration is detected using the OCS-3f sensor, and humidity is measured with the DHT22 sensor. Data from these sensors are processed by the ESP32 microcontroller and transmitted to the https://thinger.io site via built-in Wi-Fi. The monitoring tool ensures accurate measurements between 21% to 95% oxygen concentration, with a maximum error of 4.6% and a minimum error of 0.04%. This high accuracy enhances the reliability of the CPAP bubble device for oxygen therapy. The study's significance lies in its contribution to neonatal care, offering a real-time monitoring system that facilitates prompt diagnosis and treatment. By integrating IoT and telegram notifications, healthcare professionals can remotely monitor and respond to the baby's condition, improving overall care quality. This innovative tool holds promise in enhancing neonatal care, ensuring optimal oxygen therapy, and supporting the well-being of infants receiving CPAP bubble therapy. Implications of this study are promising in terms of improving neonatal care, enhancing the reliability of CPAP devices, and leveraging technology to facilitate better healthcare practices for the most vulnerable population: premature and critically ill infants.